2012
DOI: 10.1007/s00296-012-2468-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical remission in juvenile idiopathic arthritis after termination of etanercept

Abstract: Biologicals are very effective for inhibiting disease progression in active juvenile idiopathic arthritis (JIA). To date, there have been no recommendations on how and when to stop therapy with TNF inhibitors. Our objective was to analyze characteristics and the disease course of JIA patients who discontinued etanercept due to achievement of inactive disease. Data of 39 patients with JIA from two clinical pediatric rheumatology centers in Bydgoszcz and Lublin (Poland) were analyzed retrospectively. All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 6 publications
2
18
1
Order By: Relevance
“…An important consideration when tapering medications is the difficulty in re‐achieving CID if the patient flares. In contrast to previous data, suggesting that most patients are able to quickly re‐achieve remission by restarting the same medications, only 16% of our patients were able to re‐attain CID within 6 months, 62% by 12 months, and 71% by 24 months . Additionally, 17% required increased dosing or different medications to achieve CID.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…An important consideration when tapering medications is the difficulty in re‐achieving CID if the patient flares. In contrast to previous data, suggesting that most patients are able to quickly re‐achieve remission by restarting the same medications, only 16% of our patients were able to re‐attain CID within 6 months, 62% by 12 months, and 71% by 24 months . Additionally, 17% required increased dosing or different medications to achieve CID.…”
Section: Discussioncontrasting
confidence: 99%
“…It is difficult to directly compare our data to prior medication withdrawal trials, as most protocols only studied discontinuation of TNFi without incorporating other DMARDs into their analysis. Twelve‐month flare rates in these studies ranged from 57–67% in JIA, 33–34% in early RA, and 57–75% in longstanding/severe RA . In our cohort, 83% of patients on TNFi therapy flared within 12 months of discontinuing all medications, which, as expected, is higher than flare rates reported by prior studies that discontinued TNFi while continuing DMARDS.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…(6, 8, 11) Multiple studies have failed to identify other demographic and disease-specific factors associated with flare after medication discontinuation. (8, 10, 11) Two single-center observational studies have shown improved outcomes with strategies of medication reduction (rather than discontinuation): use of low-dose etanercept (9) and continued biologic use after methotrexate withdrawal. (11)…”
Section: Introductionmentioning
confidence: 99%
“…Postepski et al also evaluated clinical remission in JIA after termination of etanercept therapy 33. They retrospectively analyzed data of 39 children with JIA from two clinical pediatric rheumatology centers in Poland, all of whom stopped etanercept therapy as they achieved inactive disease.…”
Section: Etanercept Efficacymentioning
confidence: 99%